Analisis Yuridis Tentang Zakat Bagi Pegawai Negeri Sipil (Kajian dari Perspektif Hukum Islam) - Moh Ahsin; Kuswanto Kuswanto (Fakultas Hukum Universitas Darul Ulum, 2024)
Zakat, infaq and shadaqah (ZIS) are official institutions in Islamic law which relate to the property rights of a person or legal entity which have the value of worship as well as social and humanitarian charities which are useful for the welfare of mankind, maintaining security and socio-economic balance, while improving human and societal development as a whole. In Law Number 38 of 1999 concerning zakat, Article 1 explains that zakat is property that must be set aside by a Muslim or an entity owned by a Muslim in accordance with religious provisions for given to those who are entitled to receive it. Zakat imposed on salaries received by civil servants (PNS) is a type of professional zakat because it is imposed on workers' income due to their profession. As for income that is subject to zakat on the salary received for civil servants (PNS) if it has reached the nisab (the minimum amount of assets to be subject to zakat), namely 2.5% or has fulfilled the time specified according to Islamic law. Even though implementation still experiences problems and obstacles due to a lack of awareness about zakat on salaries received by civil servants (PNS), the government is obliged to collect and manage zakat, infaq and Islamic alms in a professional, honest, trustworthy and transparent manner so that The potential for zakat, infaq and alms (ZIS) which is quite large in society can be explored optimally. By creating and establishing zakat amil institutions (LAZ) in each Department or Government Agency based on the applicable laws regarding zakat management, namely Law Number 38 of 1999, so that it can improve community welfare, especially in the socio-economic field. Utilization of professional zakat proceeds will be better if it is carried out productively and managed professionally, in addition to some of it being for consumptive purposes for mustahik, especially poor and destitute groups.